Welfare Reform and Women’s Economic Development: Expanding the Discourse within Adult Education - Mary V. Alfred (Adult Education Research Conference, 2006)
researchers have examined adult development within the context of adult learning, but few have examined the economic development of women, particularly those caught in the cycle of welfare and low-wage employment. This paper will explore the personal and structurla barriers to economic development among former welfare recipients and broaden the discourse on women's development
Keywords: Welfrom reform; economic development; women& #x27; s development